FGFR1 Expression and Role in Migration in Low and High Grade Pediatric Gliomas - Egbivwie, Naomi; Cockle, Julia V.; Humphries, Matthew; Ismail, Azzam; Esteves, Filomena; Taylor, Claire; Karakoula, Katherine; Morton, Ruth; Warr, Tracy; Short, Susan C.; Brüning-Richardson, Anke (Frontiers in Oncology, 2019)
The heterogeneous and invasive nature of paediatric gliomas poses significant treatment challenges, highlighting the importance of identifying novel chemotherapeutic targets. Recently, recurrent Fibroblast growth factor receptor 1 (FGFR1) mutations in paediatric gliomas have been reported. Here, we explored clinical relevance of FGFR1 expression, cell migration in low and high grade paediatric gliomas and the role of FGFR1 in cell migration/invasion as a potential chemotherapeutic target. A high density tissue microarray (TMA) was used to investigate associations between FGFR1 and activated phosphorylated FGFR1 (pFGFR1) expression and various clinicopathologic parameters. Expression of FGFR1 and pFGFR1 were measured by immunofluorescence and by immunohistochemistry in 3D spheroids in five rare patient-derived paediatric low-grade glioma (pLGG) and two established high-grade glioma (pHGG) cell lines. Two-dimensional (2D) and three-dimensional (3D) migration assays were performed for migration and inhibitor studies with three FGFR1 inhibitors. High FGFR1 expression was associated with age, malignancy, tumour location and tumour grade among astrocytomas. Membranous pFGFR1 was associated with malignancy and tumour grade. All glioma cell lines exhibited varying levels of FGFR1 and pFGFR1 expression and migratory phenotypes. There were significant anti-migratory effects on the pHGG cell lines with inhibitor treatment and anti-migratory or pro-migratory responses to FGFR1 inhibition in the pLGGs. Our findings support further research to target FGFR1 signaling in paediatric gliomas